Waspada Cinta Maya: Membangun Kesadaran Bahaya Online Love Scam Masyarakat Desa 'Damai' Nglinggi, Kabupaten Klaten - Pramana, Pramana; Priastuty, Chairunnisa Widya; Utari, Prahastiwi (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2024)
The digital era surely facilitates all matters, but if we are not careful, this period can trap us in a misdirected pit since we are not adept enough in reading. Community service in the form of socialization in Nglinggi Village is one small step toward fostering literacy, particularly digital literacy related to media ethics and understanding of online love scams, which are becoming increasingly common today and frequently confuse victims and perpetrators. The transmitted understandings and continuous debates are unquestionably the best media for crossing paths and enhancing knowledge together. The climate of conversation that was created as a result of the passion of local inhabitants demonstrated that they were interested and focused on it. Observing existing problems and the direction of discussions with experts in their fields can lead to a suggestion that digital literacy should become a common concern and enter the tiered education curriculum so that their understanding is deeper and their internet use is more optimal and positive.